OPTIMIZING UMKM CAPACITY THROUGH DIGITALIZATION OF FINANCIAL REPORTS, HUMAN RESOURCES DEVELOPMENT, AND INTEGRATED ONLINE MARKETING - Andini, Rita; Dwi Nurdiyanto, Ahmad; Puji Lestari, Utami; Nafa, Aenun; Wahyuningsih, Melani (ICON Publisher, 2025)
This community service activity aims to increase the capacity of MSMEs in terms of digital financial reporting, human resource development, and digital marketing strategies. This program was implemented from March to April 2025 at the UMKM Pendopo of the Semarang City Cooperatives and Micro Enterprises Service with a participatory approach. The methods used include interactive training, direct practice, and intensive post-training mentoring. The results of the activity showed that participants experienced significant improvements in their ability to prepare financial reports, manage HR, and use social media for marketing. This service has a real impact on the transformation of participants' mindsets and business practices, and encourages the formation of a sustainable business community.